1985
DOI: 10.1083/jcb.100.1.258
|View full text |Cite
|
Sign up to set email alerts
|

Purification and general properties of the DNA-binding protein (P16) from rat liver mitochondria.

Abstract: The mitochondrial DNA-binding protein P16 was isolated from rat liver mitochondrial lysates by affinity chromatography on single strand DNA agarose and separated from DNA in the preparation by alkaline CsCI isopycnic gradients. The top fraction of the gradients contained a single polypeptide species (Mr ~ 15,200) based upon SDS PAGE. Digestion of single strand DNA-bound P16 with proteinase K produced a protease-insensitive, DNAbinding fragment (Mr ~ 6,000) that has been purified by essentially the same proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…E. coli SSB is known to bind DNA in several modes depending on ionic conditions (29). Studies of mtSSBs also show salt-dependent effects on DNA binding and, in particular, upon binding-site size and cooperativity of DNA binding (5,11,18). Ionic conditions likely affect both DNA conformation and SSB structure and, hence, its interactions with pol ␥.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli SSB is known to bind DNA in several modes depending on ionic conditions (29). Studies of mtSSBs also show salt-dependent effects on DNA binding and, in particular, upon binding-site size and cooperativity of DNA binding (5,11,18). Ionic conditions likely affect both DNA conformation and SSB structure and, hence, its interactions with pol ␥.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that, although there is variation in the central portion of TAS among different species, all begin with the sequence ACAT at their 5' end, are quite A+T rich, and end with a 3' A-T sequence. It is possible that differences in the nuclear-encoded gene products which may be involved in mtDNA sequence recognition (1,20,23) …”
Section: Discussionmentioning
confidence: 99%
“…In higher organisms mtSSB is primarily detected in mitochondria. Trace amounts have, however, been detected in the nucleus (77,78), and it has been demonstrated that overexpression of mtSSB can result in the activation of a nuclear gene, A␣ fibrinogen (78). Interestingly, a nuclear protein with N-terminal sequence conserved with mature mtSSB was isolated as binding to an IL-6 response element in the A␣ fibrinogen gene (78).…”
Section: An Ordered Arrangement Of Repressor Elements Binding Csd Promentioning
confidence: 99%